Identification of two compounds able to improve flax resistance towards Fusarium oxysporum infection. (December 2020) - Jaber, Rim; Planchon, Aline; Mathieu-Rivet, Elodie; Kiefer-Meyer, Marie-Christine; Zahid, Abderrakib; Plasson, Carole; Pamlard, Olivier; Beaupierre, Sandra; Trouvé, Jean-Paul; Guillou, Catherine; Driouich, Azeddine; Follet-Gueye, Marie-Laure; et al.
Highlights: Two compounds are able to trigger several defense responses in flax. They induce ROS production, callose deposition and several defense-related genes. They do not impair plant growth and do not have antifungal activities. They improve flax resistance against the pathogenic fungus Fusarium oxysporum . Abstract: Plants are surrounded by a diverse range of microorganisms that causes serious crop losses and requires the use of pesticides. Flax is a major crop in Normandy used for its fibres and is regularly challenged by the pathogenic fungus Fusarium oxysporum ( Fo ) f. sp. lini . To protect themselves, plants use "innate immunity" as a first line of defense level against pathogens. Activation of plant defense with elicitors could be an alternative for crop plant protection. A previous work was conducted by screening a chemical library and led to the identification of compounds able to activate defense responses in Arabidopsis thaliana. Four compounds were tested for their abilities to improve resistance of two flax varieties against Fo . Two of them, one natural (holaphyllamine or HPA) and one synthetic (M4), neither affected flax nor Fo growth. HPA and M4 induced oxidative burst and callose deposition. Furthermore, HPA and M4 caused changes in the expression patterns of defense-related genes coding a glucanase and a chitinase-like. Finally, plants pre-treated with HPA or M4 exhibited a significant decrease in the disease symptoms. Together, these findings demonstrate that HPA and M4 are able to activate defense responses in flax and improve its resistance against Fo infection.